Combining Carbon-Ion Irradiation and PARP Inhibitor, Olaparib Efficiently Kills BRCA1-Mutated Triple-Negative Breast Cancer Cells. (March 2022) - Kawanishi, Miki; Fujita, Mayumi; Karasawa, Kumiko
Background: Triple-negative breast cancer (TNBC) exhibits poor prognosis due to the lack of targets for hormonal or antibody-based therapies, thereby leading to limited success in the treatment of this cancer subtype. Poly (ADP-ribose) polymerase 1 (PARP1) is a critical factor for DNA repair, and using PARP inhibitor (PARPi) is one of the promising treatments for BRCA-mutated (BRCA mut) tumors where homologous recombination repair is impaired due to BRCA1 mutation. Carbon ion (C-ion) radiotherapy effectively induces DNA damages in cancer cells. Thus, the combination of C-ion radiation with PARPi would be an attractive treatment for BRCA mut TNBC, wherein DNA repair systems can be severely impaired on account of the BRCA mutation. Till date, the effectiveness of C-ion radiation with PARPi in BRCA mut TNBC cell killing remains unknown. Purpose: Triple-negative breast cancer cell lines carrying either wild type BRCA1, BRCA wt, (MDA-MB-231), or the BRCA1 mutation (HCC1937) were used, and the effectiveness of PARPi, olaparib, combined with C-ion beam or the conventional radiation, or X-ray, on TNBC cell killing were investigated. Methods: First, effective concentrations of olaparib for BRCA mut (HCC1937) cell killing were identified. Using these concentrations of olaparib, we then investigated their radio-sensitizing effects by examining the surviving fraction of MDA-MB-231 and HCC1937 upon X-ray or C-ion irradiation. In addition, the number of γH2AX (DSB marker) positive cells as well as their expression levels were determined by immunohistochemistry, and results were compared between X-ray irradiated or C-ion irradiated cells. Furthermore, PARP activities in these cells were also observed by performing immunohistochemistry staining for poly (ADP-ribose) polymer (marker for PARP activity), and their expression differences were determined. Results: Treatment of cells with 25 nM olaparib enhanced radio-sensitivity of X-ray irradiated HCC1937, whereas lower dose (5 nM) olaparib showed drastic effects on increasing radio-sensitivity of C-ion irradiated HCC1937. Similar effect was not observed in MDA-MB-231, not possessing the BRCA1 mutation. Results of immunohistochemistry showed that X-ray or C-ion irradiation induced similar number of γH2AX-positive HCC1937 cells, but these induction levels were higher in C-ion irradiated HCC1937 with increased PARP activity compared to that of X-ray irradiated HCC1937. Elevated induction of DSB in C-ion irradiated HCC937 may fully activate DSB repair pathways leading to downstream activation of PARP, subsequently enhancing the effectiveness of PARPi, olaparib, with lower doses of olaparib exerting noticeable effects in cell killing of C-ion irradiated HCC1937. Conclusions: From this study, we demonstrate that C-ion irradiation can exert significant DSB in BRCA mut TNBC, HCC1937, with high PARP activation. Thus, PARPi, olaparib, would be a promising candidate as a radio-sensitizer for BRCA mut TNBC treatment, especially for C-ion radiotherapy.